2013
DOI: 10.1097/ico.0b013e31829dd7f8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Reproducibility of Quantitative In Vivo Confocal Microscopy of Corneal Nerves in Different Corneal Locations

Abstract: Single confocal images have poor reliability for any of the 4 corneal nerve measurements, and there is no single location on the cornea that has improved reproducibility. Averaging 5 images, from different locations, improves the reproducibility and is essential for obtaining clinically meaningful data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…To date, different numbers of standard images have been analyzed by various research groups. 21,23,24,33 More recently, three to five images were suggested for the analysis at the Corneal Nerve Quantification consensus meeting in Rostock, Germany, March 17, 2013. However, to date it is not clear whether the nerve and DC densities in this sample number are comparable to the widefield composite map of the subbasal area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, different numbers of standard images have been analyzed by various research groups. 21,23,24,33 More recently, three to five images were suggested for the analysis at the Corneal Nerve Quantification consensus meeting in Rostock, Germany, March 17, 2013. However, to date it is not clear whether the nerve and DC densities in this sample number are comparable to the widefield composite map of the subbasal area.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for such a limited imaging area, multiple locations in the cornea are generally scanned and a number of representative images of the subbasal layer from these locations are used to estimate the density of nerves and DCs in the subbasal layer. 23,24 Alternatively, a wide-field mapping of composite images of a larger area has recently been employed for the subbasal layer. [25][26][27][28][29][30][31] The wide-field composite images are generated by mapping a number of the standard IVCM images manually or by using automated software.…”
Section: Purposementioning
confidence: 99%
“…Their axons synapse in the brainstem and subserve nociceptive, protective, and trophic functions . The sub‐basal corneal nerve plexus is a dynamic structure that is similar between the right and left eyes …”
mentioning
confidence: 99%
“…The more sound "study-level reproducibility" involves the analysis of images obtained from repeated patient IVCCM examinations and is a more clinically relevant measure of reproducibility as it accounts for the variation inherent in conducting multiple examinations. Such study-level reproducibility was later reported for the manual analysis technique, which revealed ICC levels in the good to very good range (exceeding levels of 0.7) [22,37,38]; quantification of nerves in the inferior whorl region of the cornea has also shown good studylevel reproducibility. [39] However, to date, only the image-level reproducibility for automated image analysis has been reported (ICC level 1.0 indicating perfect reproducibility).…”
Section: Discussionmentioning
confidence: 89%